Influence of Poloxamer 188 on Design and Develop-ment of Second Generation PLGA Nanocrystals of Metformin Hydrochloride - Bibhu Prasad Panda; Rachna Krishnamoorthy; Naveen Kumar Hawala Shivashekaregowda; Sujata Patnaik (Nano Biomedicine and Engineering, 2018)
The poly(D,L-lactide-co-glycolide) (PLGA) based second-generation nanocrystals prepared by modified nanoprecipitation method, is the method of choice for encapsulation of both lipophilic and hydrophilic drugs. In this study, nanoprecipitation technique was adopted to develop second generation nanocrystals of PLGA loaded with metformin HCl (MHc). Poloxamer 188 with three different concentrations (0.5, 0.75, 1% w/v) in combination with PLGA at 1, 2, 3% concentrations (w/v) successfully produced MHc loaded PLGA second generation nanocrystals. The effects of poloxamer 188, amphiphilic triblock copolymer on carrier particle size, surface morphology, polydispersity index, zeta potential, drug entrapment efficiency and drug release of nanoformulation were investigated. The optimized formulation of second-generation nanocrystals with concentrations 0.75% w/v poloxamer 188 and 2% w/v PLGA, could produce particle size of 114.6 nm, entrapment efficiency of 63.48% and drug release 80.23% at 12 h. A blank formulation with the same composition as optimized formulation without addition of poloxamer188 compared with optimized formulation, exhibited nanoparticles of larger mean particle size of 212.9 nm with entrapment efficiency of 68.47% and 50.5% drug release at 12 h. Transmission electron microscopy (TEM) analysis of the nanoformulations revealed that poloxamer188 greatly contributed to smooth, spherical morphology of nanosize polymeric nanoparticles. Further Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) studies on nanoformulation emphasized the significance of poloxamer188 in formulation and development of optimized MHc loaded PLGA nanosuspensions of second generation nanocrystals. In conclusion, the study emphasizes that poloxamer 188 was a versatile excipient, which played a pivotal role in producing nanosize carrier with high drug release profile of MHc loaded PLGA nanosuspensions of second generation nanocrystals.